The Influence of Brand Ambassador and Brand Image on Mobile Purchase Decisions (Case Study in Medan City) - Eddi Suprayitno (Jurnal Mantik, 2022)
Oppo is a Smartphone Manufacturer originating from China, and including a new brand in Indonesia. Oppo Smartphone can be said to be a product that is quite successful in making a history of success and is listed as the second best-selling smartphone manufacturer from China in Indonesia because the Oppo brand ambassador is easily attached to the Indonesian people. Brand ambassadors can be thought of as a type of association that arises in the minds of consumers when remembering a particular brand. If the brand image and company image in the eyes of consumers is bad, then the products produced by the company are also considered not good and the company's sales will be hampered and vice versa. This research uses quantitative descriptive research. The population in this study were visitors to four super markets in Medan City who sold the Oppo mobile brand for at least one year. The number of samples for this research is 538 respondents. Determination of the research sample using purposive sampling. The data analysis technique uses multiple linear regression with the SPSS 23 software tool. The results of this study indicate that the brand ambassador variable has a positive and significant effect on brand awareness directly. Brand ambassador has a significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions directly. Brand Ambassador and brand image have a positive and significant effect on purchasing decisions for Oppo mobile phones, a case study of Super Market visitors in Medan City.